Fé ou placebo?: os efeitos milagrosos das pílulas de Frei Galvão - Rocha, Marcelo da (2009)
The work focus on the figure of the first brazilian saint, Frei Galvao,being limited to the central question, which relates to his pills and their powers trying to find out whether the miraculous cures to them attributed are placebo effects or result from the faith the users have in the saint's power. After constructing a historical scenery on the saint's life, his miracles, emphasising the cures through the pills, and the process of canonization, the investigation on the matter begins through the theoretical discussion on faith, its sources, its historical context, the relation to popular religiosity, science, its symbols and cure powers. Following this theoretical premiss, the matter starts to be dealt with directly through the manifestations of a focus group which discusses faith in the present society, the dependence or non dependence between faith and religiosity, the question of skepticism and the abscence of faith and the possible cure relations through faith and the placebo effect. Thus, the matter is directly focused by tying the miraculous figure of Frei Galvao to the Technical data about faith, to the focus group manifestations, to the medical data on the placebo effecct, concluding that the miraculous cure effects attributed to the pills are due to the users faith also including placebo characteristics